(untitled) - Hall, Richard H (Englewood Cliffs, N.J., 1987)
Includes bibliography and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Organization; Organizational change; Tổ chức; Thay đổi tổ chức